2007
DOI: 10.1183/09031936.00031007
|View full text |Cite
|
Sign up to set email alerts
|

The need for macrolides in hospitalised community-acquired pneumonia: propensity analysis

Abstract: on behalf of the TREAT Study Group ABSTRACT: The present study compared b-lactam macrolide (''combination'') therapy versus b-lactam alone (''monotherapy'') for hospitalised community-acquired pneumonia, using propensity scores to adjust for the differences between patients.A prospective multinational observational study was carried out. Baseline patient and infection characteristics were used to develop a propensity score for combination therapy. Patients were matched by the propensity score (three decimal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…However, there are no randomized controlled trials comparing a single ␤-lactam with the same drug supplemented with a macrolide, and these recommendations are largely supported by observational studies of selected populations which have shown lower mortality rates for patients treated with ␤-lactam-macrolide combination therapy than those for patients treated with ␤-lactam monotherapy (21,35,74,180,301). However, other studies failed to show a benefit of macrolide-containing combinations (58,223). The synergy between ␤-lactams and macrolides against S. pneumoniae is not documented in vitro (172) or in vivo (115), although macrolides inhibit the production of the pneumococcal toxin, pneumolysin (8).…”
Section: Influenza and Sepsismentioning
confidence: 95%
“…However, there are no randomized controlled trials comparing a single ␤-lactam with the same drug supplemented with a macrolide, and these recommendations are largely supported by observational studies of selected populations which have shown lower mortality rates for patients treated with ␤-lactam-macrolide combination therapy than those for patients treated with ␤-lactam monotherapy (21,35,74,180,301). However, other studies failed to show a benefit of macrolide-containing combinations (58,223). The synergy between ␤-lactams and macrolides against S. pneumoniae is not documented in vitro (172) or in vivo (115), although macrolides inhibit the production of the pneumococcal toxin, pneumolysin (8).…”
Section: Influenza and Sepsismentioning
confidence: 95%
“…A study from three centers in Germany, Israel, and Italy compared mortality in CAP patients who received either a β -lactam (n=169) or a β -lactam plus a macrolide (n=282). 26 The mortality was 22% vs 7% (P=0.0001), respectively, but when the authors adjusted for confounding factors using propensity score matching to account for differences in each group, they were only able to compare 27 patients in each group, erasing any statistical difference. The differences they accounted for, and for which they excluded patients from analysis, were septic shock, mental status changes, and having an infiltrate on chest radiograph.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(87) Although most guidelines recommend empirical antibiotic coverage of atypical pathogens, there is controversy regarding the level of scientific evidence on which this practice is based. A recently published observational study involving hospitalized patients (n = 201) revealed that previous outpatient treatment with a beta-lactam antibiotic correlated with an increased possibility (approximately three times greater) of an atypical pathogen being present, whereas the possibility of pneumococci being present was reduced to one third.…”
Section: Recommendationsmentioning
confidence: 99%
“…(83,90) However, the validity of such observational studies is questionable. (87) Further prospective studies of such patients, comparing beta-lactam mono therapy with beta-lactam-macrolide combination therapy and electing the mortality rate as the primary outcome measure, are needed.…”
Section: Predictors Of Specific Pathogensmentioning
confidence: 99%